2002
DOI: 10.1210/jcem.87.3.8294
|View full text |Cite
|
Sign up to set email alerts
|

Male LH-Independent Sexual Precocity in a 3.5-Year-Old Boy Caused by a Somatic Activating Mutation of the LH Receptor in a Leydig Cell Tumor

Abstract: We describe the clinical features of severe sexual precocity in a 3.5-yr-old boy. Hormonal evaluation showed LH-independent T hypersecretion. Initial examination of the adrenals and testes revealed no evidence of congenital adrenal hyperplasia, hCG- or androgen-secreting tumors, or McCune-Albright syndrome. In the coding sequence of the LH receptor gene no activating mutation was found. Spironolactone (5.7 mg/kg x d) and testolactone (40 mg/kg x d) were unsuccessful in suppressing the elevated concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 28 publications
2
28
1
Order By: Relevance
“…In humans, a specific activating mutation of the Lhcgr, D578H, was found to lead to the formation of LC adenomas (Liu et al, 1999;Richter-Unruh et al, 2002). Whether such adenomas are derived from fetalor adult-type LCs remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, a specific activating mutation of the Lhcgr, D578H, was found to lead to the formation of LC adenomas (Liu et al, 1999;Richter-Unruh et al, 2002). Whether such adenomas are derived from fetalor adult-type LCs remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although the regression of fetal LCs in man starts normally already in fetal life (Chemes, 1996;Habert et al, 2001), we do not know how an activating Lhcgr mutation affects their lifespan. Nevertheless, the hCG þ mice provide a phenocopy of the human activating mutation of Lhcgr presenting with prepubertal LC adenomas and testotoxicosis (Liu et al, 1999;Richter-Unruh et al, 2002). Another phenotypic feature of the activating Lhcgr mutations is precocious puberty in boys between 1 and 4 years of age (Themmen and Huhtaniemi, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with previous studies, based on long-term LH/hCG treatments in vivo (Risbridger et al 1982, Gaytan et al 1994, these mice developed focal Leydig cell hyperplasia/hypertrophy, but failed to promote testicular tumours. This was intriguing, since in humans, a specific activating mutation of the LHR (Asp 578 His) is associated with Leydig cell adenomas (Liu et al 1999, Richter-Unruh et al 2002. Interestingly, recent studies in young hCGab þ mice demonstrated postnatally clear Leydig cell adenomas of foetal Leydig cell origin, but these tumours disappeared at puberty .…”
Section: Transgenic Mice Overexpressing Hcgmentioning
confidence: 99%
“…Females with the activating mutations do not have an apparent phenotype. A particularly potent activating somatic mutation (D578H) has been identified in boys with testicular adenomas wherein the mutation is limited to the adenoma and not the surrounding normal tissue (Liu et al, 1999;Canto et al, 2001;Richter-Unruh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%